Climate change and its implications for developing brains – In utero to youth: A scoping review - Sean A. Kidd; Jessica Gong; Alessandro Massazza; Mariya Bezgrebelna; Yali Zhang; Shakoor Hajat (The Journal of Climate Change and Health, 2023)
The brain health and development implications of climate change are situated within a large and rapidly increasing body of evidence that addresses the physical and mental health impacts and implications of extreme and worsening environments. The costs to individuals and societies of negatively impacted brain development are profound – be it in the form of diagnosable developmental disability, reduced cognitive capacity, or areas of behavioral functioning. We have sought to describe the key risk domains that climate change presents with respect to healthy brain development, from the prenatal through to youth stages. Scoping review methods and an a priori search strategy were used to address the question: What are the major considerations of the peer-reviewed literature that address climate change as it relates to brain development and health from early development through to youth populations? Themes from the identified papers were charted, and findings were summarized through a consensus process. A total of 40 papers were identified in the search, spanning 2008–2022. Based on the thematic analysis, results are organized into the following nine themes: 1) heat extremes, 2) weather extremes and stress, 3) air pollution, 4) vector and waterborne illnesses, 5) malnutrition, 6) equity, 7) economic implications, 8) methods issues, and 9) responses. There is a clear consensus amongst the papers in this review suggesting that changing climate patterns and weather extremes have substantial and wide-ranging effects on developing brains. A range of responses are proposed with an emphasis upon early intervention and better data.